Infection After Cardiac Transplantation: Treatment and Prognosis - Reece, Ian J. (1984)
Since July 1982, 18 patients have undergone orthotopic cardiac transplantation at the Texas Heart Institute with steroid and cyclosporine immunosuppression. There have been no deaths from infection despite 15 bacterial, 8 viral, 6 fungal and 1 protozoal infection episodes. With a total follow-up of 90 patient months (mean follow-up, 5.0 months; range 0.1 to 18 months), the incidence of infection is 33 episodes per 100 patient months (1.7 episodes per patient). Only 23 episodes (77%) required drug treatment. Compared to conventional immunosuppressive regimes, cyclosporine treatment is associated with a substantial reduction in the incidence and severity of infection in cardiac allograft recipients.